Bring it on : fight to the finish - Woodruff, Bille; Song, Elena; Longo, Cody, 1988- (Millers Point, N.S.W. Distributed by Universal Pictures (Australasia), 2009)
"Christina Milian stars as sassy cheer captain Lina Cruz, whose world is turned upside-down when her family moves from the urban streets of East Los Angeles to the sunny beach town of Malibu . At her new school, Lina clashes with Avery, the ultra-competitive all-star cheer captain, while also falling for Avery's super-cute brother, Evan. Lina's always been able to rise to a challenge, but can she create a new all-star squad, beat Avery at the Spirit Championships and still keep her romance with Evan? Hot music, fierce competition and high-flyin' fun continue in this all-new movie!"--Container.
"8272315."
Includes special features.
Directed by Bille Woodruff ; written Elena Song and Alyson Fouse.
Christina Millian, Cody Longo.
Censorship classification: PG.
PAL ; Regions 2, 4 and 5.
Keywords: Cheerleading -- California -- Drama; High school students -- California -- Drama; California; Drama; Feature films; Teen films; Feature films